Advantages and Dısadvantages of E-MAX and Zırconıa Crowns - Dolidze, Tamar; Bitarova, Ilona (European Scientific Journal, ESJ, 2017)
The success of a dental restoration depends upon a number of factors such as the material chosen, its mechanical properties, anatomical form, surface texture, translucency and color. In order to overcome the unaesthetic metallic seen in PFM restorations, dental research began to be directed towards metal-free ceramic restorations to improve the aesthetic outcome. We will discuss the differences and make some suggestions relative to when and where Zircon dioxide and IPS E-max crowns are best suited and discuss about advantages and disadvantages of this two types of crowns.